BUILDING THE SOCIETY LEGAL CULTURE THROUGH LEGAL COUNSELING MODEL AS A SOCIAL MARKETING - Setiawati, Rini (INTERNATIONAL JOURNAL OF RESEARCH IN LAW, ECONOMIC AND SOCIAL SCIENCES, 2019)
Fostering the legal awareness is a current social change demand as part of government attention and promotion in various development efforts. Therefore, the establishment of a new legal product will become a reality if supported by the society members legal awareness. Legal awareness is the basis of the implementation of the law and it related to legal culture closely. Building the society legal culture should be oriented for the efforts to instill, promote and institutionalize the values underlying the law that require legal communication. The current legal counseling are required not just to do with the formal legal approach, but it can be done through a social marketing approach that more responsive in dynamics of change and the need for legal information in each segment of society.